Energy, heat transfer and economic analysis of flat-plate solar collector utilizing SiO2 nanofluid / Mohd Faizal Fauzan - Mohd Faizal, Fauzan (2015)
Solar thermal energy can be a good replacement for fossil fuel because it is clean and sustainable. However, the current solar technology is still not efficient and expensive. The effective way to increase the efficiency of solar collector is to use nanofluid. This study is carried out to analyze the impact on thermal performance, heat transfer and economic of a flat-plate solar collector when SiO2 nanofluid utilized as working fluid. The analysis is based on different volume flow rates and varying nanoparticles volume fractions. From the numerical study, it can be revealed that CuO have the highest thermal efficiency enhancement of up to 38.46% compared to water where else SiO2, TiO2 and Al2O3 performed almost similarly. However, SiO2 nanofluid is the cheapest and the most abundance materials on earth. Therefore, it is more suitable option. The experimental study has indicated that up to 27.2% increase in the thermal efficiency and 34.2% increase in exergy efficiency were achieved by using 0.2% concentration SiO2 nanofluid on solar collector compared to water as working fluid. The drawback of adding nanoparticles in the base fluids is the increase in viscosity of the working fluid that has led to increase in pumping power of the system and pressure drop in pipes. However, for low concentration nanofluids, only negligible effect in the pumping power and pressure drop is noticed. Using nanofluid could also improve the heat transfer coefficient by 28.26%, saving 280 MJ more embodied energy, offsetting 170 kg less CO2 emissions and having a faster payback period of 0.12 years compared to conventional water based solar collectors. Applying SiO2 nanofluid could improve the thermal efficiency, heat transfer and economic performance of a flat-plate solar collector.